What Does It Mean To Be Global? - Rana Diorio (CA, United States Little Pickle Press LLC, 2009)
Can you say "hello" in nine languages? You can! Join children from around the world as they play, sing, and travel, trying all types of food and experiencing other traditions. Living respectfully and peacefully with one another, they celebrate diversity, see how their actions affect another person's experience, and come to understand that being global means being a citizen of the world.
Keywords: Circle Time; Stereotypes / Identity / Diversity/ Gender Roles -- Stereotypes / Identity / Diversity/ Gender Roles